(3GdHQgGf aj CSQGQ Yde GdejRGfs - (3Ydj Hf eMeO Hf CjOeQ GdpLrdnOcj, YR GdOjf,J (B742 (3g` s
(3ChdgG (B:s
(3Gf JaUd Gdbhd ai GdRGL JaUjdkG eWdbkG s
(3BNQgG (B:s
(3hHg Je GdLRA GdKGfi ef cJGH GdHQgGf ai CSQGQ Yde GdejRGf hGdMeO ddg QH GdYGdejf s
(3eQJH Ydi CQHYI YTQ HGHkG hNGJeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B28s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B173 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B18 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdcjejGA h GdWHjYjGJs